2019
DOI: 10.1108/lodj-07-2018-0254
|View full text |Cite
|
Sign up to set email alerts
|

Experiences that develop leadership capabilities

Abstract: Purpose The purpose of this paper is to answer the research question: what recent experiences – other than undertaking training and development programmes – do mature managers and professionals regard as important for their development as leaders? Design/methodology/approach A survey was issued to mature managers and professionals, asking them to rate the contribution of certain experiences to their recent development of leadership capabilities, and to provide qualitative data on the most important experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Studies on leadership found that leadership had a relationship and/or effect on quality management, especially when organizations begin to implement quality management programs (Chaijukul, 2010; Laohavichien et al , 2011; Kemenade, 2014; Boak and Crabbe, 2019). Individual staff members who have leadership proficiency have various leadership attributes, for example, possessing good judgment skills, achieving decisive outcomes, sustaining an intrinsic driving force, maintaining an open-mind regarding change and adaption, and asserting a proactive attitude toward common goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on leadership found that leadership had a relationship and/or effect on quality management, especially when organizations begin to implement quality management programs (Chaijukul, 2010; Laohavichien et al , 2011; Kemenade, 2014; Boak and Crabbe, 2019). Individual staff members who have leadership proficiency have various leadership attributes, for example, possessing good judgment skills, achieving decisive outcomes, sustaining an intrinsic driving force, maintaining an open-mind regarding change and adaption, and asserting a proactive attitude toward common goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A series of studies undertaken by scholars and practitioners with junior and senior executives over the past four decades (e.g. Boak and Crabbe, 2019; Lindsey et al , 1987; McCall et al , 1988; Nowill, 2011; Zemke, 1985) indicate that the answer may lie in having individuals undergo “challenging” or “stretching” experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Although all employees may be eligible for developmental opportunities such as training, the most visible and impactful development usually goes to high-potential employees. These valuable developmental opportunities go to high-potential employees because organizational leaders believe these employees can be successful in taking on challenging experiences and that these experiences will help employees to develop their knowledge, skills, and abilities to take on future leadership positions within the firm (Boak & Crabbe, 2019;Day, 2000;Hezlett, 2016).…”
Section: Promotability and Developmentmentioning
confidence: 99%
“…This disparity not only affects promotion decisions, including lateral promotions, but also other development offered to men and women in the workplace. Developmental work opportunities are important for employees to develop leadership skills and to demonstrate that they are ready for a leadership position higher up in the organization (Boak & Crabbe, 2019;Day, 2000;Hezlett, 2016). Across organizations, men tend to receive more challenging work assignments (King et al, 2012), developmental job assignments (Lyness & Schrader, 2006), and international assignments (Meier, 2017) than women.…”
Section: Promotability and Developmentmentioning
confidence: 99%
See 1 more Smart Citation